22xy6 • (2x3y - 3)
Reformatting the input :
Changes made to your input should not affect the solution:
(1): "y6" was replaced by "y^6". 1 more similar replacement(s).
Step by step solution :
Step 1 :
Equation at the end of step 1 :
(((4 • (x3)) • y) - 6) • 2xy6
Step 2 :
Equation at the end of step 2 :
((22x3 • y) - 6) • 2xy6
Step 3 :
Step 4 :
Pulling out like terms :
4.1 Pull out like factors :
4x3y - 6 = 2 • (2x3y - 3)
Trying to factor as a Difference of Cubes:
4.2 Factoring: 2x3y - 3
Theory : A difference of two perfect cubes, a3 - b3 can be factored into
(a-b) • (a2 +ab +b2)
Proof : (a-b)•(a2+ab+b2) =
a3+a2b+ab2-ba2-b2a-b3 =
a3+(a2b-ba2)+(ab2-b2a)-b3 =
a3+0+0+b3 =
a3+b3
Check : 2 is not a cube !!
Ruling : Binomial can not be factored as the difference of two perfect cubes
Multiplying exponents :
4.3 21 multiplied by 21 = 2(1 + 1) = 22
Final result :
22xy6 • (2x3y - 3)